Security on IBM z/VSE - Hellner, Helmut (IBM Corporation, International Technical Support Organization, 2018)
Abstract One of a firm's most valuable resources is its data: client lists, accounting data, employee information, and so on. This critical data must be securely managed and controlled, and simultaneously made available to those users authorized to see it. The IBM® z/VSE® system features extensive capabilities to simultaneously share the firm's data among multiple users and protect them. Threats to this data come from various sources. Insider threats and malicious hackers are not only difficult to detect and prevent, they might be using resources with the business being unaware. This IBM Redbooks® publication was written to assist z/VSE support and security personnel in providing the enterprise with a safe, secure and manageable environment. This book provides an overview of the security that is provided by z/VSE and the processes for the implementation and configuration of z/VSE security components, Basic Security Manager (BSM), IBM CICS® security, TCP/IP security, single sign-on using LDAP, and connector security.
"This edition (SG24-7691-02) applies to IBM z/VSE V6R2"--Page 2 of cover. - Includes bibliographical references. - Online resource; title from cover (Safari, viewed July 11, 2018)
Keywords: Computer security; Sécurité informatique